Pelatihan Ekoleksikon Laut Pulau dalam Peningkatan Pengetahuan Ekologis bagi Guru dan Siswa Di SMAN 27 Maluku Tengah - Hiariej, Chrissanty; Pesiwarissa, Leonora Farilyn (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
Literacy development still needs to be considered in learning in accordance with the vision and mission of schools, universities, and the development of local wisdom. The strengthening of literacy developed in this service activity will be adjusted to the vision and mission of Pattimura University, which is based on the island sea. Therefore, the service developed was made the center of human resource development, science, technology, and art. In addition, it has a cultural character based on the island's sea. This is also important to support the value of the forming index, especially the cultural dimension. Therefore, the service team, which also acts as a resource person, will provide training in terms of language and literature with the target activities of teachers and students of SMA Negeri 27 Central Maluku. The service carried out aims to document the island's marine ecosystem in increasing ecological knowledge for teachers and students at SMA N 27 Central Maluku. The output of the activity is in the form of an article that will be sent to the Gaba-gaba Journal of Community Service, Department of Language and Arts Education, FKIP Unpatti, using the training method and arranged with planned stages. The result of the service is the implementation that produces an island sea ecolexicon in the Seith language, which has been discussed in the training.